TEACHERS' STRATEGIES IN TEACHING ENGLISH DURING THE PANDEMIC AT ONE OF THE ISLAMIC SECONDARY SCHOOLS IN JAMBI - Failasofah, Failasofah; Yanto, Yanto; Nurulsabila, Diniyah (Magister Pendidikan Bahasa Inggris Universitas Jambi, 2024)
In this research, researchers explore the teachers' strategies in teaching English during the COVID-19 pandemic at one of the Islamic secondary schools in a suburban area in Jambi. In conducting the research, researchers employed a qualitative research design with a case study method. The interview was conducted to investigate teachers' strategies during the irregular educational environment as the effect of the global pandemic. Based on the research findings, teachers often used strategies in English learning classes during the COVID-19 pandemic and utilized video as the learning media. Teachers use these strategies because it is more exciting and easier for students to understand the learning material. Teachers sometimes use several other strategies that are less efficient for online learning.